ANALYSIS OF THE ERUPTION MECHANISM AND MODELING OF TEFRA FALL PHASE 2B-3 OF GALUNGGUNG VOLCANO FOR THE PERIOD 1982-1983 WEST JAVA PROVINCE - Sakinah, Salma
The eruption of the Galunggung Volcano in 1982-1983, which lasted for nine months, caused morphological changes up to a radius of 20 km from the center of the eruption and disrupted two flights. Several studies have found that the final phase of the eruption had a basalt composition of magma. During this phase, the volcano erupted an ash column of 10 km in height, but with a small volume of ejected material. Therefore, the authors conducted a study with the aim of determining the eruption mechanism and conducting modeling of the final phase of the 1982-1983 eruption. The study utilized ash fall deposits from the final phases, which were divided into phase 2b and phase 3. The tephra analysis included various grain analyses, bubble number density (BND), microlite number density (MND), decompression rate, and magma ascent rate. Additionally, the tephra distribution was modeled using the TephraProb application. From the results of various grain analyses, it was found that the products of phase 2b-3 eruptions were dominated by coarse-lapilli vesicular scoria ash, with grain shapes becoming denser towards the end of phase 2b. In phase 2b, BND has a value of 0,62-3,9x1012 m-3, and MND has a value of 0,29-1,1x1013 m-3. In phase 3, BND has a 1,0-3,1x1012 m-3, and MND has a value of 0,58-1,1x1013 m-3. The analysis of decompression rate and magma ascent rate results shows that the range of values for phase 2b is 0,15-1,8x104 Pa/s and 0,06-0,70 m/s, and for phase 3 is 1,1-1,8x104 Pa/s and 0,5-0,7m/s. Therefore, the results of various analytical methods indicate that the eruption mechanism experiences a decline in energy during the initial phase 2b (phreatomagmatic). However, towards the later stages of phase 2b, there is a subsequent rise in eruption caused by significant impact of meteoric water. Later, the eruption energy decreases again towards phase 3 (strombolian). Furthermore, based on the eruption distribution modeling, the parameters with the highest level of danger on October 14th, 1982, revealed that volcanic ash was scattered over a 60 km radius, predominantly leaning towards the west. The eruption had a volume of 3x106 m3, an ash column height of 9 km, and a total mass of approximately 38,75x108 kg.